THE CONCEPT OF MANAGEMENT IN HIGHER EDUCATION INSTITUTIONS AND ITS FUNDAMENTAL PRINCIPLES (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article examines the key principles of governance in higher education institutions, focusing on leadership roles, human resource management, and the implementation of innovations in education. The governance system in higher education is a multi-level and complex structure aimed at balancing academic freedom and state control. Furthermore, the study highlights the significance of digital transformation, international cooperation, and innovative approaches in higher education governance. The article discusses modern management principles such as transparency, efficiency, strategic planning, and human resource development to improve educational institutions' overall effectiveness.